Pengaruh Kepemilikan Saham Asing, Kualitas Informasi Internal, Publisitas CEO, ROA, Leverage dan Ukuran Perusahaan terhadap Penghindaran Pajak - Muhammad Akbar; Teddy Chandra; Rini Yayuk Priyati (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2021)
The purpose of this study is to determine the effect of foreign share ownership, quality of internal information, publicity of chief executive officer, return on assets, leverage and company size on tax avoidance in mining companies listed on the IDX from 2010 to 2018. Analytical tools used in This study is a multiple linear regression with tax avoidance as measured by dividing the amount of tax paid with profit before tax which is the dependent variable and six independent variables, namely foreign share ownership as measured by dividing total foreign shares by total shares outstanding, quality of information. internal which is measured by the number of days from December 31 to the date of publication of the company's annual financial statements, CEO publicity is measured through google trends, ROA is measured as a percentage of the ratio between net income after tax and total assets, leverage is measured by n divide total debt by total assets, and firm size is measured by the log of total assets. The data used is secondary data obtained from mining financial reports listed on the Indonesia Stock Exchange (BEI), with documentation techniques. The results of data processing obtained model Y = 0.329 - 0.082 KSA - 0.002 KII + 0.001 PCEO + 0.118 ROA + 0.107 LEV + 0.011 UKP + e. Partially, the results of the t test show that the variables of foreign share ownership, internal information quality, CEO publicity, leverage, and company size have an effect on tax avoidance, but return on assets has no effect on tax avoidance. The analysis results show that the tax avoidance variable is influenced by the independent variable by 14%.